Analyisis Of Boiler Reliability Maintenance System With Availability Ratio At PT. XXX: Analisa Sistem Perawatan Keandalan Boiler Dengan Rasio Availability Di PT. XXX - Setiawan, Luthfi Frans; Widodo, Edi (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates a food manufacturing firm's efforts to enhance operational efficiency by optimizing its maintenance strategy and spare parts management within the context of noodle production. The research focuses on reducing prolonged machine downtimes caused by boiler malfunctions, which negatively impact production targets. A novel approach combining total minimum downtime calculations and a hybrid corrective-preventive maintenance methodology has been proposed. To bolster this initiative, an efficient spare parts procurement scheme was implemented. Results demonstrate a substantial reduction in unplanned downtime following implementation, thereby improving overall productivity and profitability. Implications highlight the potential for widespread application across similar industries seeking to minimize disruptions while maximizing equipment lifetimes. highlight : Reduced downtime through improved boiler maintenance. Hybrid corrective-preventive maintenance for efficient operations. Optimized spare parts procurement for enhanced productivity. Keywords: noodle production, boiler maintenance, downtime reduction, spare parts management, hybrid maintenance.